Innovative Technologies in Post-Harvest Processing: AI, 3D Printing, And Renewable Energy for Sustainable Practices - Rohit Dutta Choudhury,; Asaruddin Sheikh,; Kanica Roy,; Joytu Debnath, (International Journal of Scientific Research in Science and Technology, 2025)
Post-harvest loss is among the major threats to global food security and economic stability. New technologies, such as AI, 3D printing, and renewable energy, offer innovative solutions that enhance efficiency, minimise waste, and promote sustainability in post-harvest systems. This paper reviews these technologies and their applications: AI-driven grading and predictive analytics, 3D-printed tools and packaging innovations, and renewable energy-powered drying and storage systems. It further elaborates on the key developments, implementation challenges, and future directions, and underlines the transformative nature of these technologies in creating resilient and sustainable agricultural systems that would be able to meet some of the pressing concerns in food production and distribution. These innovations would assure food security for both developed and developing countries. Significant environmental impacts and costs of running agricultural supply chains would be dramatically reduced. Innovation has also provided equal access to resources and opportunities among smallholder farmers and helped promote global environmental goals. Together with the advocacy and filling up of gaps concerning technology and infrastructural accessibility, this paper has pointed out the need for multidisciplinary cooperation and laws that support such actions.
Keywords: Post-harvest Processing; Artificial Intelligence; 3D printing; Renewable Energy; Sustainable Agriculture